Growth and Mortality of Mouth Brooding Tilapiines of the Kafue Floodplain Fishery, Zambia - C. Makeche, Mauris; G. Mudenda, Hangoma; Katongo, Cyprian (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Growth and mortality of Oreochromis andersonii, Oreochromis macrochir and Oreochromis niloticusof the Kafue Floodplain fishery were investigated between September, 2015 and November, 2015. This study was aimed at investigating the growth and mortality of mouth brooding tilapiines of the Kafue Floodplain fishery. Three stations that represent the major ecological habitats of the Kafue Floodplain fishery were selected. These were: Kafue Road Bridge (swamp), Namalyo (lagoon) and Kakuzu (riverine). Fish specimens were collected using gillnets that were set in the evening and hauled the next morning. Length measurements were taken from each fish specimen using a fish measuring board. Weight was measured using a kitchen balance to the nearest one gramme. One-way Analysis of Variance was performed on all quantitative data using Statistix 9.0 software. Oreochromis niloticus showed the largest growth coefficient (k) of 0.22 while Oreochromis macrochir had the smallest growth coefficient of 0.10. Oreochromis andersonii had a growth coefficient of 0.11. Exploitation ratios in the Kafue Floodplain fishery were found to be below the optimum value (0.5) except for Oreochromis macrochir (0.7). Oreochromis andersonii had an exploitation ratio of 0.3 while Oreochromis niloticus had an exploitation ratio of 0.4. This implies that the decrease in fish catches in the Kafue Floodplain fishery cannot be attributed to over-fishing but may be due to natural mortality.